TRIM65 determines the fate of a novel subtype of pituitary neuroendocrine tumors via ubiquitination and degradation of TPIT. Issue 8 (26th February 2022) - Yao, Hong; Xie, Wanqun; Dai, Yuting; Liu, Yanting; Gu, Weiting; Li, Jianfeng; Wu, Liang; Xie, Jing; Rui, Weiwei; Ren, Bohan; Xue, Li; Cheng, Yijun; et al.
Abstract: Background: Pituitary neuroendocrine tumors (PitNETs) are common intracranial tumors that are classified into seven histological subtypes, including lactotroph, somatotroph, corticotroph, thyrotroph, gonadotroph, null cell, and plurihormonal PitNETs. However, the molecular characteristics of these types of PitNETs are not completely clear. Methods: A total of 180 consecutive cases of PitNETs were collected to perform RNA sequencing. All subtypes of PitNETs were distinguished by unsupervised clustering analysis. We investigated the regulation of TPIT by TRIM65 and its effects on ACTH production and secretion in ACTH-secreting pituitary cell lines, as well as in murine models using biochemical analyses, confocal microscopy, and luciferase reporter assays. Results: A novel subtype of PitNETs derived from TPIT lineage cells was identified as with normal TPIT transcription but with lowered protein expression. Furthermore, for the first time, TRIM65 was identified as the E3 ubiquitin ligase of TPIT. Depending on the RING domain, TRIM65 ubiquitinated and degraded the TPIT protein at multiple Lys sites. In addition, TRIM65-mediated ubiquitination of TPIT inhibited POMC transcription and ACTH production to determine the fate of the novel subtype of PitNETs in vitro and in vivo . Conclusion: Our studies provided a novel classification of PitNETs and revealed that the TRIM65-TPIT complex controlled the fate of the novel subtype of PitNETs, which provides a potential therapy target for Cushing's disease.